Bimodal growth of Au on SrTiO3(001). - Silly, F; Castell, M (2006)
We have investigated the vapor phase growth of Au on SrTiO3(001)-(2 x 1) substrates by UHV scanning tunneling microscopy. Submonolayer (ML) coverages below 300 degrees C wet the surface as disordered metastable 2D islands. Beyond 0.75 ML fcc nanocrystals with a (111) interface are nucleated and ripen by dewetting the surrounding layer. Some multiply twinned fivefold symmetric clusters are also created. Above 400 degrees C dewetting occurs for all coverages and the surface is only populated by nanocrystals and fivefold clusters. A planar ground state configuration for small Au clusters and a higher interface energy for crystals than for wetted 2D ML films explains these results.